Integrating passive seismicity with Web-Based GIS for a new perspective on volcano imaging and monitoring: the case study of Mt. Etna - Guardo, Roberto Antonino (2017)
Fil: Guardo, Roberto Antonino. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.